2000
DOI: 10.1038/sj.jea.7500106
|View full text |Cite
|
Sign up to set email alerts
|

Interim results of the study of particulates and health in Atlanta (SOPHIA)

Abstract: Substantial evidence supports an association of particulate matter ( PM ) with cardiorespiratory illnesses, but little is known regarding characteristics of PM that might contribute to this association and the mechanisms of action. The Atlanta superstation sponsored by the Electric Power Research Institute as part of the Aerosol Research and Inhalation Epidemiology Study ( ARIES ) study is monitoring chemical composition of ambient particles by size fraction, as well as a comprehensive suite of other pollutant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
68
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 18 publications
1
68
1
Order By: Relevance
“…Researchers in only three studies in Asia found an association with both O 3 and NO 2 (29,33,40). Studies in Europe and North America showed an association either with NO 2 (24,30,35,43) or O 3 alone (17,27,39,47,48).…”
Section: Gaseous Pollutantsmentioning
confidence: 99%
“…Researchers in only three studies in Asia found an association with both O 3 and NO 2 (29,33,40). Studies in Europe and North America showed an association either with NO 2 (24,30,35,43) or O 3 alone (17,27,39,47,48).…”
Section: Gaseous Pollutantsmentioning
confidence: 99%
“…One set of studies relies on central site monitors for specific pollutants and uses statistical techniques to infer a relation with traffic rather than other pollution sources (Laden et al, 2000;Tolbert et al, 2000;Yu et al, 2000;Janssen et al, 2002). Although these studies yield interpretable estimates of population-wide effects, they provide no ability to discern highly exposed subpopulations or geographic clustering of impacts potentially associated with pollution ''hot spots''.…”
Section: Introductionmentioning
confidence: 99%
“…Further investigation of pollutant mixtures and effect modification may also provide insights (8, 9); for example, there have been reports of stronger pollution effects during the warm season (10-15) even though pediatric asthma rates peak during the cold season (16). To lessen concerns about uncontrolled confounding, aggressive control for variables, such as meteorology and seasonal asthma trends, is required.In the present study, we analyzed data from the Study of Particles and Health in Atlanta (SOPHIA) (14,(17)(18)(19)(20)(21), one of the largest single-city time-series studies of the health effects of urban air pollutants, to investigate short-term associations between ambient air pollutant concentrations and pediatric emergency department visits for asthma or wheeze in metropolitan Atlanta, Georgia, during 1993-2004. Our study takes advantage of daily measurements of components of particulate matter less than 2.5 mm in aerodynamic diameter (PM 2.5 ), a resource not typically available to investigators, which enables us to distinguish among the various compounds that comprise PM 2.5 .…”
mentioning
confidence: 99%